Giulia Champion, Roxanne Douglas, and Stephen Shapiro, Decolonizing the Undead: Rethinking Zombies in World Literature, Film and Media, London: Bloomsbury Academic, 2023, 224 p. - ANDREESCU, Robert-Giulian (Studia Universitatis Babeș-Bolyai Philologia, 2025)
This collection of essays, edited by Giulia Champion, Roxanne Douglas and Stephen Shapiro, comes as a contribution towards a decolonizing movement that differentiates itself from the postcolonial attitude. As Shapiro points out, starting from a contrast expressed by Nick Couldry and adding a ‘Warwick School perspective’, whereas postcolonialism posited a colonial endeavor that focused on difference as a mechanism for meaning-creating epistemic violence, decolonizing goes beyond criticizing “capitalism, globalism, and neoliberalism” by aiming to find “intellectual resources from beyond the Western Canon”, especially if they come from the ‘Global South’ (2023, 40-41). To be specific about the Warwick School perspective adopted here, Shapiro explains a fundamentally world-systems-based approach towards capitalism that reveals it to be a system which “operates through the creation of social inequalities (rather than simply social differences) to achieve its drive for endless accumulation for accumulation’s sake” (41). Furthermore, the decolonizing approach recognizes that capitalism inherently functions because of weakly proletarianized labor, as much as the centrist liberalism he critiques in the third chapter would theorize otherwise (41). The reason for the necessity of this theoretical preamble is the fact that it reflects upon the other entries into this collection. As much as a claim can be made for the individuality of the perspective, the methodology and of the cultural material chosen to be discussed on the part of each author, engaging in the (same) specific endeavor of decolonizing the figure of the zombie in World Culture requires shared fundamental values and perspectives towards said figure that can be found in Shapiro’s more theoretical essay. To clarify and reiterate, it is not a case of uniformity, but rather an interplay of nuance that lets each author complement or contrast the work of their co-contributors.